Changes in the anterior segment of the eye following uncomplicated pars plana vitrectomy. A review - Kopecky, Adam; Nemcansky, Jan (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2019)
Pars plana vitrectomy is currently the most common technique used in retinal surgery. Although primarily involving the posterior segment of the eye it also affects the anterior segment. As this is a less published topic, the aim of this paper was to review the literature on changes in the anterior segment after uncomplicated pars plana vitrectomy using data based literature search. The conclusions are that even in otherwise ophthalmologically healthy patients, complications may occur in the anterior segment. Surgeons need to pay utmost attention in glaucoma patients and in those with endothelial insufficiency who are at highest risk of complications. He/she must also correctly plan a potential cataract surgery if not already done earlier. From the literature, most of the changes in the anterior segment after uncomplicated PPV are found to be temporary.
Keywords: oční čočka; anterior segment; rohovka; Intraocular Pressure; přední segment oční; ophthalmology; Cornea; ultrasound biomicroscopy; Lens, Crystalline; lidé; vitrektomie; pars plana vitrectomy; Vitrectomy; extrakce katarakty; nitrooční tlak; Anterior Eye Segment; rohovkový epitel; Epithelium, Corneal; Cataract Extraction; corneal endothelium; Humans